2008
DOI: 10.5713/ajas.2008.70348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red Deer Antlers on Cutaneous Wound Healing in Full-thickness Rat Models

Abstract: The process of wound repair involves an ordered sequence of events such as overlapping biochemical and cellular events that, in the best of circumstances, result in the restoration of both the structural and functional integrity of the damaged tissue. An important event during wound healing is the contraction of newly formed connective tissues by fibroblasts. The polypeptide growth factors, like transforming growth factor-β (TGF-β), insulin-like growth factor I (IGF-I) and epidermal growth factor (EGF), play v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…So far, many investigations have shown the presence of mineral elements, polypeptides, proteins, amino acids, polysaccharides, and fatty acids in velvet antlers (Sui, Zhang, Huo, & Zhang, ). In addition, a number of studies have demonstrated that velvet antlers have diverse pharmacological effects, including tissue repair, treatment of bone‐resorption diseases, and rheumatoid arthritis (Gu et al, ). It not only prolongs the lifespan of tumor‐bearing mice (Cui et al, ), but also prevents cancer cell metastasis (Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, many investigations have shown the presence of mineral elements, polypeptides, proteins, amino acids, polysaccharides, and fatty acids in velvet antlers (Sui, Zhang, Huo, & Zhang, ). In addition, a number of studies have demonstrated that velvet antlers have diverse pharmacological effects, including tissue repair, treatment of bone‐resorption diseases, and rheumatoid arthritis (Gu et al, ). It not only prolongs the lifespan of tumor‐bearing mice (Cui et al, ), but also prevents cancer cell metastasis (Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The homogenate was centrifuged at 12,000 g for 30 min and the extracts were used for the ELISA assay (Gu et al, 2008). The ELISA analysis was performed using a commercially available kit (Human IGF-I Immunoassay, R&D Systems, USA) on tissues extracted and prepared using established protocols.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the proliferation effect of deer antler is studied recently [ 8 , 9 ]. Previously, our research group demonstrated the beneficial effect of deer antler on wound healing in a rat model [ 10 ]. In the same study, we coincidentally observed that deer antler extract seemed to have a stimulatory effect on hair regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies investigating the effect of deer antler on wound healing [ 10 ], we found that deer antler extract accelerated hair growth by enhanced IGF-1 expression in wound healing skin [ 13 ]. In the current study, we aimed to investigate the further molecular mechanism of deer antler aqueous extract on regulation of the hair cycle and hair follicle cell proliferation.…”
Section: Introductionmentioning
confidence: 99%